Real-Time Heart Rate Monitoring for Wearable Electrocardiography Using Filter-Based and Peak Threshold Algorithms: A Comparative Study - Desima Klaudia Hasibuan; Indra Hardian Mulyadi (Politeknik Negeri Batam, 2018)
Wearable and wireless Electrocardiograph (ECG) enables real-time and long-term monitoring of heart rate (i.e. 24 hours). Several algorithms have been introduced to increase the accuracy of the heart rate calculation for this type of ECG. This study aims to compare the accuracy of two heart rate calculation algorithms: Filter-Based and Peak Threshold. Both algorithms were implemented into a wearable ECG prototype comprising AD8232, 8-bit microcontroller (ATMega328), and Bluetooth. ECG signals and heart rate (in Beat per Minute (BPM)) were sent via Bluetooth and displayed in real-time on a Windows-based application created using Visual C #. Experiments were conducted on 10 healthy subjects aged 20.4 ± 2.0 years and body weight of 60.8 ± 10.2 kg. The measurement results calculated by using Filter-Based and Peak Threshold were compared to a commercial wearable ECG (KineticTM) as a ‘ground truth’. The test results showed that the Filter-Based algorithm resulted in a more accurate calculation with the Root Mean Square Error (RMSE) of 1.53, compared to the Peak Threshold algorithm with RMSE of 2.69.